CHALLENGES OF USING EMI IN TEACHING AND LEARNING OF UNIVERSITY SCIENTIFIC DISCIPLINES: STUDENT VOICE - Al Zumor, Abdulwahid Qasem (International Journal of Language Education, 2019)
This study examines the challenges of using English medium instruction (EMI) in teaching and learning scientific disciplines. The main objective of the study is to identify studentsâ€™ perceptions regarding lecture comprehension, communication, pedagogy, assessment, and affect in an EMI setting. The participants in this study are 264 Saudi students who study Computer Science, Engineering, and Medicine. A questionnaire with a four-point Likert scale was used to survey the participantsâ€™ views on the challenges they encounter as a result of the use of EMI for teaching and learning scientific disciplines. The collected data were analysed quantitatively with SPSS and qualitatively by using the content analysis method. The major findings of the study are: a) using English language to teach scientific disciplines has a seriously negative impact on the scientific content comprehension and assessment of a majority of the students in the present study, b) using English language as the medium of instruction and assessment causes anxiety, frustration, tension, fear, embarrassment and, ultimately, poor educational outcomes, c) EMI deprives the students of their basic rights to effective understanding, communication, interaction, discussion and inquiry. The study recommends ensuring quality English education in the foundation year and examining the option of â€œadditive bilingual education.â€